2006
DOI: 10.1191/0960327106het648oa
|View full text |Cite
|
Sign up to set email alerts
|

Toward an evidence-based toxicology

Abstract: The increasing demands on toxicology of large-scale risk assessment programmes for chemicals and emerging or expanding areas of chemical use suggest it is timely to review the toxicological toolbox. Like in clinical medicine, where an evidence-based medicine (EBM) is critically reviewing traditional approaches, toxicology has the opportunity to reshape and enlarge its methodology and approaches on the basis of compounded scientific knowledge. Such revision would have to be based on structured reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
91
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 140 publications
(113 reference statements)
0
91
0
Order By: Relevance
“…Without an explanation of how evidence is "weighed" or "weighted", the WOE approach may be to be a "black box" of scientific judgment 13) . To keep transparency of expert reviews, the review should be objective and taken into consideration of evidence based toxicology 16) .…”
Section: Transparency and Objectivitymentioning
confidence: 99%
“…Without an explanation of how evidence is "weighed" or "weighted", the WOE approach may be to be a "black box" of scientific judgment 13) . To keep transparency of expert reviews, the review should be objective and taken into consideration of evidence based toxicology 16) .…”
Section: Transparency and Objectivitymentioning
confidence: 99%
“…Uncertainties should be transparently addressed and documented. Furthermore, different cost components need to be acknowledged, in particular welfare losses from misclassifications (Hoffmann and Hartung, 2006), monetary costs of regulatory validation of testing strategies (Schaafsma et al, 2009), animal welfare loss (Hartung et al, 2013;Rovida et al, 2015) and direct testing costs Hartung et al, 2013;Rovida et al, 2015). Jaworska and Hoffmann (2010) indicated that the process of integrating information from toxicity testing should allow for evidence maximisation while considering factors such as costs, animal welfare and test complexity for an optimal selection of information sources (computational, in chemico and in vitro methods).…”
Section: Criteria Related To Generating Informationmentioning
confidence: 99%
“…Lewis et al, 2007;Kinsner-Ovaskainen et al, 2009;Schaafsma et al, 2009;Krewski et al, 2010;De Wever et al, 2012 Protect animal welfare; reduce/minimise the number of animal used in testing or animal suffering when animal testing is considered unavoidable. Hoffmann and Hartung, 2006;Lewis et al, 2007;Hoffmann et al, 2008;Schaafsma et al, 2009;Krewski et al, 2010 Evaluation of cost-effectiveness or efficiency. Hoffmann and Hartung, 2006;Lewis et al, 2007;Hoffmann et al, 2008;Schaafsma et al, 2009;Krewski et al, 2010 Conceptual requirements for DA development Data integration and final conclusion based on a coherent methodology (e.g.…”
Section: Criteria Related To Generating Informationmentioning
confidence: 99%
See 2 more Smart Citations